Experiences of Healthcare Providers Who Provide Emergency Care to Migrant Children Who Arriving in Spain by Small Boats (Patera): A Qualitative Study - María del Mar Jiménez-Lasserrotte; Rosalía Artés-Navarro; José Granero-Molina; Isabel María Fernández-Medina; María Dolores Ruiz-Fernández; María Isabel Ventura-Miranda (Children, 2023)
Background: The phenomenon of migration from regions with more limited resources is a reality of the globalized world. It is estimated that at the end of 2019, almost 80 million migrants were displaced around the world, with 46% of them being children. Almost 20% of the irregular immigrants who arrived in Spain were child irregular migrants, who travelled alone or accompanied by family members after leaving their countries of origin seeking, to find a better future. Child irregular migrants have specific healthcare needs. The objectives of our present study were to describe and understand the experiences of healthcare providers in relation to the healthcare needs and the process of emergency care for child irregular migrants who come to Spain in small vessels. Methods: In this descriptive qualitative study, two focus groups were convened, and in-depth interviews with 21 participants were conducted, followed by inductive data analysis using ATLAS.ti 9.3 software. Results: Three main themes emerged from the analysis: (1) more vulnerable groups for whom the priority is emergency care; (2) the health and social care of child migrants; and (3) challenges and advances in the care of child migrants. Conclusions: For healthcare providers, protecting children, placing value on the family unit, and ensuring that children feel safe at all times are very important. Learning about the experiences of healthcare providers can contribute towards improving the health and social care of children in emergency care.